Dual pathology at the injection site: Insulin-derived amyloidosis with superimposed acanthosis nigricans in a patient with type 1 diabetes - Alshehri, Layan; Al-Husain , Khalid; Aljuhani, Turki; Alsayyah, Ahmed; Almutlaq, Hamad (Acta Biomedica Atenei Parmensis, 2026)
Insulin-derived amyloidosis (IDA) and acanthosis nigricans (AN) are conditions that may develop at injection sites, though their co-occurrence is exceptionally rare. This case report highlights the rare coexistence of insulin-derived amyloidosis and acanthosis nigricans by presenting the clinical features, histopathological findings, and underlying pathophysiological mechanisms. It emphasizes the importance of recognizing atypical injection-site dermatoses and their impact on glycemic control and patient care. We report the case of a 51-year-old woman with long-standing T1DM who presented with progressively thickened, hyperpigmented plaques at her abdominal and thigh injection sites. Histological evaluation of punch biopsies confirmed the presence of amyloid deposits consistent with IDA, with overlying epidermal changes of AN. These findings highlight a rare dual pathology at insulin injection sites. This case underscores the importance of recognizing unusual skin changes at insulin injection sites, particularly in patients with poorly controlled diabetes. Early recognition, supported by biopsy and histopathology, is crucial for accurate diagnosis and effective management.